Relationships of body composition and liver fat content with insulin resistance in obesity‐matched adolescents and adults. (19th March 2014) - Linder, Katarzyna; Springer, Fabian; Machann, Jürgen; Schick, Fritz; Fritsche, Andreas; Häring, Hans‐Ulrich; Blumenstock, Gunnar; Ranke, Michael B.; Stefan, Norbert; Binder, Gerhard; Ehehalt, Stefan
<x xml:space="preserve">Abstract</x> Objective While in adults not total body‐ or visceral fat mass, but liver fat content was found to independently determine insulin resistance, it is unclear whether these relationships are already present in obese adolescents. Methods Thirty‐nine overweight/obese adolescents were matched for sex and BMI with 39 adults. To compare the age‐ and sex‐specific BMI values of adolescents and adults, the percentile value of each adolescent was projected to the age of 18. Body fat depots were quantified by whole‐body magnetic resonance (MR) imaging. Liver fat content was measured with 1H‐MR spectroscopy. Insulin resistance was estimated from the homeostasis model assessment of insulin resistance (HOMA‐IR). Results Compared to overweight and obese adults, adolescents had higher HOMA‐IR (P < 0.001) and lower lean body mass (P = 0.002). Furthermore, they had higher total body‐ (P = 0.02), but lower visceral‐ (P < 0.001) fat mass, while liver fat content was not significantly different between the groups (P = 0.16). In both groups liver fat content (both P ≤ 0.007), but not total body‐ or visceral fat mass (all P ≥ 0.64) was an independent predictor of insulin resistance. Conclusions Having lower visceral fat mass, overweight and obese adolescents are more insulin resistant than sex‐ and BMI‐matched adults. Liver fat content, but not total body‐ or visceral fat mass, is an independent determinant of insulin resistance in adolescents.